CNSC-27. AN IDO-PROTAC HIGHLIGHTS A NOVEL TRYPTOPHAN METABOLISM- INDEPENDENT ROLE FOR IMMUNOSUPPRESSIVE IDO IN HUMAN GLIOBLASTOMA. (14th November 2022) - Bommi, Prashant; Monsen, Paige; Bommi, Lakshmi; Zhai, Lijie; Bell, April; Lauing, Kristen; Mi, Xinlei; Kocherginski, Masha; Horbinski, Craig; Lukas, Rimas; Schiltz, Gary; Wainwright, Derek
Abstract: INTRODUCTION: Indoleamine 2, 3-dioxygenase 1 (IDO) is an immunosuppressive enzyme that catabolizes the essential amino acid, tryptophan (Trp), into the metabolite, kynurenine. IDO is expressed in >90% of patient resected GBM. IDO suppresses the anti-brain tumor immune response, in-part, through non-metabolic activities. To determine how IDO non-metabolically suppresses the anti-GBM immune response, IDO-protein degrader (IDO-proteolysis targeting chimera; IDO-PROTAC) effects were studied in multiple human models of GBM. METHODS: The IDO-expressing GBM cell lines, U87, U138, as well as the patient derived xenograft (PDX) line, GBM43, were treated with either IDO-PROTAC, mutant PROTAC, IDO enzyme inhibitor, or IDO siRNA, followed by RNA-seq analysis and/or mass spectrometry with quantitative proteomics using tandem mass tag (TMT) labelling. RESULTS: Transcriptomic analysis revealed differentially expressed genes that were commonly regulated after treatment with the IDO-PROTAC as compared to treatment with the mutant PROTAC or IDO enzyme inhibitor groups in U87, U138, and GBM43 cells. Mass spectrometry analysis found 34 unique proteins that were differentially expressed inside of human GBM cells, with an additional 20 unique proteins that were identified in the supernatant of cultured human GBM cells after IDO-PROTAC treatment. Meta-analysis of the transcriptomic and proteomic analyses identified a novel factor that was unique to IDO-PROTAC treatment. GO terms that were enriched after IDO-PROTAC treatment identified nucleoside kinase activity as well as metallocarboxypeptidase activity. CONCLUSIONS: This study discovered multiple new targets and pathways that immunosuppressive IDO regulates through a non-metabolic function. Functional analyses that validate the newly-discovered IDO-dependent, IDO-enzyme independent factors, are ongoing.